التسويف الأكاديمي وعلاقته بالقلق بوصفه (سمة وحالة) "دراسة ميدانية على عينة من طلبة كلية التربية في جامعة تشرين" - بوبو منذر; شريبه بشرى; شبيب هناء صالح (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
هدفت الدراسة الحالية إلى الكشف عن العلاقة بين التسويف الأكاديمي والقلق بوصفه (سمة وحالة) لدى عينة من طلبة كلية التربية في جامعة تشرين، كما هدفت إلى معرفة الفروق بين أفراد العينة في التسويف الأكاديمي، وفي القلق بوصفه (سمة وحالة) تبعاً لمتغير الجنس. وقد تكونت عينة الدراسة من (92) طالباً وطالبةً من كلية التربية تم اختيارها بالطريقة العشوائية البسيطة، وطبق عليها مقياس التسويف الأكاديمي، واختبار حالة وسمة القلق. وقد كشفت نتائج الدراسة على وجود ارتباط دال إحصائياً بين التسويف الأكاديمي والقلق بوصفه (سمة وحالة) لدى أفراد العينة، ولم تبين وجود فروق جوهرية تعزى لمتغير الجنس في التسويف الأكاديمي، وفي القلق بوصفه (سمة وحالة). This study aimed to (a) investigating the relationship between academic procrastination and anxiety as (trait and state) among a sample of students from the Faculty of Education at Tishreen University, and (b) to find out the differences between the members of the sample in academic procrastination, and anxiety as (trait and state), according to students’ gender. Participants were (92) students from the College of Education, The measures were academic procrastination, and anxiety test as (state and trait), The results showed that there is correlation between academic procrastination and anxiety as (trait and state) among the members of the sample as a whole, but no significant differences were found due to students’ gender in academic procrastination, and anxiety as a (state and trait).